Optimizing regeneration techniques and fxed‑bed column application for leachate treatment utilizing carbon mineral composite - Detho, Amir; Abdul Kadir, Aeslina; Daud, Zawawi; Memon, Asif Ali; Rosli, Mohd Arif; Rassem, Hesham Hussein (springer, 2025)
The performance of carbon mineral-combined adsorbents in a batch and fxed column study was examined for removing chemical oxygen demand (COD) and ammoniacal nitrogen (NH3-N), which typically found in landfll leachate. The batch experiment was carried out using various factors including adsorbent dosages and retention time, while column performance was evaluated by optimizing the infuent fow rate. The surface of the composite adsorbent was examined using X-ray fuorescence (XRF), Fourier transform infrared (FTIR), and scanning electron microscopy (SEM) to determine any changes before and after column operations. The XRF analysis of the composite adsorbent reveals a high concentration of calcium oxide and silica oxide as the primary compounds. The main functional groups in the composite adsorbent included O–H, N–H, O–C, C–N, C–O, and Si–O–Si. The SEM analysis revealed that the composite adsorbent contains heterogeneous pores and a rough surface. The reduction rates achieved were 86% for COD, with an optimum adsorption capacity of 31.3 mgg−1, and 80% for NH3-N, with an optimum adsorption capacity of 29.8 mgg−1. The breakthrough capacities for COD and NH3-N adsorption were 6.55 and 4.24 mgg−1, respectively. However, optimal empty-bed contact times (EBCTs) in minutes were 480. The performance efciency of the column for COD and NH3-N was 0.9978% and 0.9913%, by utilizing fresh composite adsorbent, and these number fgures increased to (≥0.9998%) respectively after the regeneration process. The Adams–Bohart constant for COD from 5.30× 10–6 to 4.92× 10–6 mL/min-mg and NH3-N from 2.90× 10–5 to 4.52× 10–5 mL/ min-mg respectively was found to increase with increasing fow rates from 1.5 to 3.0 mLmin−1. Therefore, COD and NH3-N adsorption on composite adsorbent at fow rates of 1.5 mLmin−1 was considered appropriate from the context of this study. In summary, this research has successfully shown that the use of composites as an adsorbent is a viable and suitable for the removal of COD and NH3-N from leachate, indicating their potential for use in real-world industrial wastewater treatment could further enhance their practical applications.